Karakteristik Khutbah Jumat di Mesjid Kampus: Perspektif Komunikasi - Hamdan, Yusuf (Mediator, 2007)
This research which uses descriptive approach is focused on Friday speech characteristic delivered on campus mosque. The details of research focus are (1) Profile of the speaker; (2) Audience perception toward the speaker (as communicator); (3) Audience perception toward Friday speech’ features (message). It is found that the speakers are mostly middle aged, docent, has formal education background, but also graduated from an Islamic dormitory. They have speech experience for a long time, using multimedia devices, writing-communication-skilled, and being highly exposed by the media. The audience perceived the speakers as somebody who mastered the materials and acquired speech skill. But the messages are not clear and concise, the peakers itself was perceived as insensitive toward his audience. Speech message was positively perceived, the theme was relevant enough and attracted audience. But the topics aren’t actual enough, and didn’t have a unity of idea.